Intensified antituberculosis therapy in adults with tuberculous meningitis - Heemskerk, AD; Bang, ND; Mai, NTH; Chau, TTH; Phu, NH; Loc, PP; Chau, N; Hien, T; Dung, N; Lan, N; Lan, N; Lan, N; et al. (Massachusetts Medical Society, 2016)
Background: Tuberculous meningitis is often lethal. Early antituberculosis treatment and adjunctive treatment with glucocorticoids improve survival, but nearly one third of patients with the condition still die. We hypothesized that intensified antituberculosis treatment would enhance the killing of intracerebral Mycobacterium tuberculosis organisms and decrease the rate of death among patients.